Monoclonal antibodies and the ErbB system in human cancer - Greene, Mark (Henry Stewart Talks, 2019)
General properties of tumor cells, Human breast cancer and the erbB2/neu oncogene and protein, Targeted monoclonal antibodies, Tyrosine kinase activity and dimerization, Activation of the kinase of erbB2/neu, Overexpression of erbB2/neu and EGFr, The erbB family members, Discussion of Herceptin, Prevention of tumor growth in a neoadjuvant model, Two antibody therapy & tumor growth inhibition